Novel parameters characterizing size distribution of A and B starch granules in the gluten network: Effects on dough stability in bread wheat. (1st April 2021) - Yu, Liwei; Guo, Lei; Liu, Yingchun; Ma, Yanrong; Zhu, Jianchu; Yang, Yang; Min, Donghong; Xie, Yanzhou; Chen, Mingxun; Tong, Jingyang; Rehman, Ata-ur; Wang, Zhonghua; et al.
Graphical abstract: Highlights: Physicochemical properties of gluten and starch in 16 wheat varieties were analyzed. B- to A-type starch divided by gluten lacunarity (B/A/Lacunarity) was characterized. B/A/Lacunarity represented distribution of various-sized starch in gluten network. B/A/Lacunarity was positively correlated with dough stability time. B/A/Lacunarity is suggested as an index to evaluate dough structure and properties. Abstract: Our study on six wheat genotypes has revealed strong interaction between gluten and starch to affect dough stability. To establish gluten-starch interaction and its roles in dough stability, we randomly selected 16 wheat genotypes and investigated the physicochemical properties of gluten and starch. The manner in which the starch granules occupied available space in gluten network was quantitatively analyzed using gluten lacunarity and proportion of different sized A-type and B-type starch granules. Positive correlations were found between the morphological attributes (B/A/Lacunarity, B/Lacunarity) and dough stability. The correlation coefficient between B/A/Lacunarity and dough stability was highest, followed by the percentage of unextractable polymeric protein (UPP%), B/Lacunarity and dough stability. Dough mixing properties were strongly affected by gluten-starch interactions, as indicated by novel parameters. Whereas the effect of gluten on its own did not provide any evidence to suggest its concrete role in dough mixing properties because of the various genetic backgrounds.